Distinct Routes to Understand the Relationship Between Dispositional Optimism and Life Satisfaction: Self-Control and Grit, Positive Affect, Gratitude, and Meaning in Life - Oriol, Xavier; Miranda, Rafael; Bazán, César; Benavente, Estefany (Frontiers in Psychology, 2020)
Over the last years, understanding the implications of prospective thinking toward the future has become increasingly interesting. This study aims to delve into the relation between dispositional optimism, one of the most relevant prospective constructs, and life satisfaction. Additionally, we also seek to prove the mediating effect of different cognitive and affective variables associated to both hedonic and eudaimonic well- being on this relation. A first study is conducted with 275 secondary students to assess the relation between optimism and life satisfaction through self-control and grit (14.82, SD = 1.07), which indicates the existence of a mediating effect from grit but not from self-control. A second study is conducted with 1,356 university students (21.5, SD=2.35) to demonstrate the mediating effect of positive affect on dispositional optimism and life satisfaction. Results show a strong relation between optimism and positive affect, but no mediating effect on life satisfaction. Finally, a third study comprising 371 secondary students (14.12, SD=1.78) demonstrates the existence of a serial multiple mediation from gratitude and meaning in life over the relation between optimism and life satisfaction. Implications are discussed in order to discuss how prospective variables like dispositional optimism may lead to an increase in subjective well-being through different affective and cognitive mechanisms.